Chlamydial abortion of ewes and goats. I. Current aspects on etiology, pathogenesis, immune mechanisms and epizootiology of disease - SIARKOU (Β. ΣΙΑΡΚΟΥ), V. (Journal of the Hellenic Veterinary Medical Society, 2018)
Chlamydial abortion constitutes one of the major causes of infectious abortion in sheep and goats. The disease leads to considerable losses in most sheep and goat-rearing countries, as well as, in Greece. In this paper, a review of the causative agent, pathogenesis, host immune response and epizootiology is presented. After recent changes, that have occured in the taxonomy of chlamydiae, it is necessary to refer to new families, new genera and new species within the order Chlamydiales, with emphasis on new species of Chlamydophila abortus, the causal agent of chlamydial abortion. This study reviews the recent experimental data which indicate the sites of entry of the organism, the way of its dissemination and establishment to the placenta. It also reviews current research on the humoral and cell-mediated immune responses, the role of the IFN-γ in latent infection and this of Tcells in the protective immune response. Finally, particular reference is given on the role of the male in the disease transmission and the role of inter-species contamination in chlamydial abortion.